Pharmacist-Nurse Collaborative Medication Reconciliation: Impact On Post-Discharge Readmission Rates (The Review of Diabetic Studies, 2025)
Background: The transition of care from the acute hospital setting to the community is a period of heightened vulnerability for patients, characterized by a fragmentation of clinical information and a high incidence of medication discrepancies. Hospital readmissions, particularly those occurring within 30 days of discharge, serve as a critical metric for healthcare quality and a significant driver of healthcare expenditures globally. Empirical evidence suggests that a substantial proportion of these readmissions—ranging from 16% to over 20%—are attributable to medication-related problems (MRPs), including adverse drug events (ADEs), non-adherence, and unintentional discrepancies between the discharge regimen and the patient’s home routine. While medication reconciliation (MedRec) is a mandated patient safety goal, standard care models often rely on siloed practitioners, leading to suboptimal outcomes. The emergence of interprofessional collaborative practice, specifically the pharmacist-nurse dyad, posits that combining the pharmaceutical expertise of the pharmacist with the holistic assessment and educational capabilities of the nurse creates a synergistic safety net superior to uni-disciplinary approaches.Objective: This systematic review aims to comprehensively evaluate the impact of pharmacist-nurse collaborative medication reconciliation interventions on post-discharge hospital readmission rates. Secondary objectives include assessing the impact on emergency department (ED) utilization, the resolution of medication discrepancies, the incidence of adverse drug events (ADEs), economic outcomes, and patient satisfaction.Methods: A rigorous systematic review of the literature published through 2023 was conducted. The search strategy targeted randomized controlled trials (RCTs), quasi-experimental studies, prospective cohorts, and quality improvement initiatives involving adult patients discharged from acute care settings. Interventions were required to demonstrate active, bidirectional collaboration between nursing and pharmacy staff, such as joint bedside rounds, integrated discharge workflows, or sequential reconciliation processes. Data extraction focused on readmission metrics (7-day, 30-day, 90-day, and 180-day), discrepancy categorization (omission vs. commission), and qualitative themes regarding implementation barriers.Results: The review synthesized findings from 57 studies, including 14 RCTs and 43 non-randomized interventions. The aggregated data indicates that pharmacist-nurse collaborative models significantly reduce the likelihood of all-cause 30-day readmissions, with relative risk reductions ranging from 20% to nearly 70% in high-intensity cohorts. A landmark RCT demonstrated a reduction in 30-day readmission rates from 47.6% in the control group to 28.6% in the intervention group (p=0.028). Extended interventions that continued the collaboration into the post-discharge phase (e.g., telephonic follow-up) showed sustained benefits up to 180 days. The collaboration was particularly effective in resolving unintentional discrepancies, with resolution rates exceeding 85% for identified errors. Economic analyses revealed substantial cost avoidance, with one study projecting annualized net savings of over $1.5 million due to averted readmissions. However, the review also identified significant heterogeneity in implementation strategies and persistent barriers related to role clarity, hierarchy, and information technology interoperability.Conclusion: The pharmacist-nurse collaborative model represents a high-value, evidence-based strategy for mitigating the risks associated with hospital discharge. The dyad effectively bridges the gap between prescribing intent and patient adherence, addressing both the clinical logic of the medication list and the practical realities of the patient’s life. Healthcare systems are strongly encouraged to adopt structured interprofessional MedRec protocols to enhance patient safety and ensure financial sustainability.